Growth of zinc oxide nano-rods on optical fibers for optical interconnects and side coupling applications / Hoorieh Fallah - Hoorieh, Fallah (2016)

(untitled)
The thesis introduces a novel concept that utilizes the scattering properties of Zinc Oxide (ZnO) nanorods to control light guidance and leakage inside optical fibers. ZnO rods scatter the light at larger angle than the critical angle inside the fiber. Hence, part of the incident light is coupled into fiber modes. A dense and highly ordered array of ZnO NR’s is grown onto the cladding surface of the fiber using a simple low temperature hydrothermal technique, which involves two processes: seeding nanoparticles and growth of the nanorods. Nanorods length and density are found to be the most crucial parameters for the optimum side coupling. These parameters are controlled through the seeding and growth time to maximize the light side coupling to the cladding modes. Optimums seeding of nanoparticles concentrations are 1 mM zinc acetate, 10 mM of zinc nitrate and 10 mM of hexamine. The optimum rods growth time was 8 hour in oven. Maximum excitation of the cladding mode by side coupling of light was obtained with nanorods of length ~2.2 μm, demonstrating average coupling efficiency of ~2.65%. To increase coupling efficiency though core modes excitation, the fiber cladding is chemically etched to allow light to reach the core region. Growth of ZnO NR’s on the etched region allows the collection of light incident angles as large as 90 degrees to scatter inside the core region. This combination of nanostructures and fiber systems is used to demonstrate a simple wide field of view (FOV) optical receiver. The angular response of the receiver is tested using an in-house built nephelometer. Light coupling efficiency is extracted by de-convolving the finite beam extinction from the measured power. The results were compared to the first order analytical model where the phase function is assumed to linearly shift with the incident angle. The trend of the experimental measurements agrees with the model. 180o FOV is verified and maximum coupling efficiency of around 2.5% for a single fiber is reported. Excitation of core iv modes through side coupling allows for application of these devices towards wide FOV optical receivers.